Different Effects of Cold Stimulation on Reflex and Non-Reflex Components of Poststroke Spastic Hypertonia - Li, Sheng; Shin, Henry; Zhou, Ping; Li, Xiaoyan (Frontiers in Neurology, 2017)
Objective: To use an established biomechanical approach to quantify reflex and non-reflex responses from spastic paretic elbow flexors in response to controlled cold and heat stimulation. Methods: Thirteen spastic-hemiplegic stroke subjects were tested in the experiment. The spastic elbow joint was stretched into extension for 50 degrees at two speeds (5˚/s and 100˚/s) in a customized apparatus. Thermal stimulation (HEAT at heat pain threshold, COLD at 0˚C, or BASELINE at room temperature) was applied to the thenar eminence of the contralateral hand immediately prior to stretching for at least 30 seconds. Results: Total torque was greater at 100˚/s than at 5˚/s. Total torque was significantly increased after COLD, but not HEAT as compared to BASELINE. When normalized to total torque at baseline, HEAT decreased total torque by 6.3%, while COLD increased total torque by 11.0%. There was no significant difference in the reflex torque among three thermal conditions. Conclusion: The findings demonstrate differentiated effects of cold stimulation on the total resistance from spastic muscles. They provide objective evidence for anecdotal clinical observations of increased muscle spasticity by cold exposure